The utility of patient-reported outcome measures in orthopaedic trauma research: a systematic review. Issue 6 (9th November 2022) - Magnusson, Erik A.; Novak, Avrey; Bagley, Joshua; Walterscheid, Zakkary; Jackson, Madeleine; Claudi, Carolin; Elhaddad, Moamen; Albaba, Adam; Doan, Jessica; Vo, Kiet; Firoozabadi, Reza
Abstract : Background: Patient-reported outcome score measures (PROM) are valuable tools in assessing patient function following management of orthopaedic conditions. The purpose of this study was to investigate and characterize the use of PROM in the orthopaedic trauma literature. Methods: Articles published in the Journal of Orthopaedic Trauma (JOT), Journal of Bone and Joint Surgery (JBJS), Clinical Orthopaedics and Related Research (CORR), Foot and Ankle International (FAI), Journal of Hand Surgery (JHS), and Journal of Shoulder and Elbow Surgery (JSES) from 2011 to 2019 were reviewed. Publications pertaining to outcomes after trauma were included. Publication year, number of patient-reported outcome measures (PROM) used, and the specific PROMs published per study were recorded. Results: Of the 11, 873 articles reviewed, 3, 583 (30%) articles pertained to trauma. Twenty-nine percent of orthopaedic trauma articles utilized at least one PROM. There was a gradual increase in trauma publications with PROMs over 9 yr. An average of two PROMs were reported per publication. The percentage of trauma studies that included PROMs varied by journal. In JOT, 35% of trauma articles published included PROM, 30% of articles published in JBJS, 27% in CORR, 48% in JSES, 30% in JHS, and 49% of trauma articles in FAI utilized PROM. The most commonly used PROMs included: visual analog scale (VAS) (n=411), Disabilities of the Arm and Hand Score (DASH) (n=281), Constant-Murley Score (n=145), Short Form Survey-36 (n=123), the Mayo Elbow Performance Index (n=101), and American Shoulder and Elbow Surgeons Standardized Shoulder Assessment (n=93). Conclusions: Clinical outcome studies utilizing PROMs after orthopaedic trauma represented a minority of publications across six major journals between 2011 to 2019. Standardization of PROMs is lacking, making comparison between studies challenging. The VAS and DASH scores were the most frequently PROMs reported followed by additional PROMs for the upper extremity. Characterizing the use of PROMs directs future investigators toward selecting applicable PROMs to evaluate patient outcomes following orthopaedic trauma. Level of Evidence: Level IV.